Factors affecting a successful coordination of sports and academic careers - Gorenc, M.; Braz, M. (Expanding Horizons. Business, Management and Technology for Better Society, 20-22 May 2020, Online Conference, 2020)
The career of a top athlete is relatively short and few athletes can secure financial resources during their active sports career, which is why it is imperative to think about how they will manage to do that. They have a much better starting point for competing in the labour market with a successfully completed education and vocation. We conducted a survey among 112 Slovenian athletes. Based on the research, we found that an athlete's academic performance is influenced by the characteristics of the study programme, such as the difficulty of the study programme, the volume of all study burden, the possibility of adjusting study obligations and the flexibility of the higher education institution.